Analysis of talent management design in achieving radio broadcasting professionalism at LPP RRI Gunungsitoli: - Zendrato, Puji Restu Four; Harefa, Peringatan; Waruwu, Sukaaro; Lase, Delipiter (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyze archival management in an effort to improve the management of administrative administration and to find out the obstacles to archival management in an effort to improve the management of administrative administration at the Housing and Settlement Area Office of Gunungsitoli city. The type of research used in this research is descriptive research, with a qualitative approach. The data collection methods used include observation, interviews, and documentation. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions/verification. The results show that the design of talent management at LPP RRI Gunungsitoli begins with the talent selection process that focuses on criteria such as unique vocal characters, good communication skills, as well as script reading skills and an attitude of responsibility. Increasing professionalism in radio broadcasting at LPP RRI Gunungsitoli is carried out through a series of steps that include strengthening capabilities, improving broadcast quality, improving facilities and infrastructure, optimizing the number of human resources, and applying the latest information technology.